Le site de la Scène nationale (Augustonemetum/Clermont-Ferrand, Puy-de-Dôme) : une auberge et son enseigne peinte - Julien Ollivier; François Blondel; Sylvain Foucras; Charlotte Hallavant; Marie-Adeline Le Guennec; Samuel Longepierre; Laëtitia Pédoussaut (Gallia)
A building interpreted as a hostel was discovered in 2013-2014, during a survey excavation carried out in the suburbs of Augustonemetum/Clermont-Ferrand. The building, erected in the late 1st c. AD or early in the 2nd c., is located near the main southern access road to the agglomeration and along the last street of the urban grid. It is characterized by large courtyards, several cells of small dimensions interpreted as apartments and an extensive local that seems partly devoted to food preparation. The identification of the hostel is supported by the discovery of a wooden sign on which a painted inscription includes the term uiator, designated as the typical customer in literary and epigraphic documentation.